Analysis of Apron Movement Control (AMC) Personnel Availability Towards Airside Supervision Operational Activities of PT Angkasa Pura I Pattimura Ambon International Airport - Kampono, Muhamad Fajrul; Yudianto, Kifni (CV. Rayyan Dwi Bharata, 2024)
Apron Movement Control (AMC) is a unit that is responsible for flight operations, aircraft movement supervision, vehicle traffic, passengers and cleanliness supervision in the airside area and recording flight data on the apron. AMC officers are one of the factors that also determine the achievement of organizational goals in the airport sector, because the human resources of AMC officers are the subject of every activity in the organization, the assessment for subjects is carried out through their performance assessment. Through a combination of human resources, facilities/equipment and procedures in a series of elements that work together in carrying out the functions and tasks of supervision and service on the airside so that the goals are achieved. This study aims to determine the supervision of the AMC unit at Pattimura Ambon International Airport in terms of human resources and supporting facilities as well as obstacles in carrying out supervision in the airside area and efforts to overcome obstacles. This study uses a descriptive qualitative approach. The data used are primary and secondary data. Primary data is obtained from observation and interviews, while secondary data comes from literature studies and photographs related to the problems studied. The data analysis techniques used are data reduction, data presentation and drawing conclusions. To test the validity of the data, the triangulation technique is used. The research time was in March 2024. The results of the study showed that the supervision of the AMC unit at Pattimura Ambon International Airport was carried out in accordance with PM-IK (Quality Procedures and Work Instructions), starting from supervision of FOD (foreign object debris), fuel spills, vehicle speed according to SKEP/140/VI/1999, supervision of aircraft movements, supervision of the use of PPE according to procedures and supervision of wind running up / idle. The number of AMC unit human resources currently has 7 personnel consisting of 6 implementing personnel and 1 leader. The AMC unit has equipment that is suitable for use including Handy Talky (HT), Telescope (Binoculars), Computer, Ear Muff, Bad Marshaller, Sunglasses, Light Stick, Raincoat, Follow Me Car, Speed Trap and CCTV. The obstacle in AMC supervision is the lack of personnel so that the workload increases and there are still service users / workers who violate the rules on the airside. The AMC unit has attempted to submit additional personnel and the AMC unit strictly enforces service user discipline according to procedure.